HUBUNGAN ASUPAN VITAMIN D DAN KALSIUM DENGAN KADAR GLUKOSA DARAH PUASA WANITA OBESITAS USIA 45-55 TAHUN - Rochmah, Nur; Probosari, Enny; Dieny, Fillah Fithra (Journal of Nutrition College, 2017)
Background : Vitamin D and calcium have metabolic functions in the cells and insufficient intake has been proven to increase the risk factor for many chronic diseases, such as diabetes mellitus. Vitamin D and calcium both contribute in raising insulin secretion by regulating extracelullar calcium concentration and fluxing through cell membranes facilitated by calcium-sensing receptor. This study aimed to determine correlation between vitamin D and calcium intake with blood glucose levels in obese woman aged 45-55 years.Methods : Observational study with cross sectional design. Sixty subjects were selected using consecutive sampling. Food intakes were assessed by Semi Quantitative Food Frequency Questionnaire, fasting blood glucose levels were measured by Glucose Oxidation method, and physical activities were determined by Long International Physical Activity Questionnaire. The data were analyzed using r Pearson and Rank-Spearman test. Results : Mean of fasting blood glucose levels was 90,4±37,22 mg/dL with average vitamin D was 4,1 ±2,23 μg, whereas calcium was 547,7±316,24 mg. All subjects had low vitamin D intake; 88,3% subjects had low calcium intake; 88,3% subjects had normal fasting blood glucose; and 11,7% subjects had hyperglycemia. There was no correlation between vitamin D (p = 0,295) and calcium  (p = 0,295) intake with fasting blood glucose levels. Intake of energy, carbohydrate, fat, protein, fiber  and physical activity also showed no corerelation with fasting blood glucose levels. Conclusion : There was no correlation of vitamin D and calcium intake with fasting blood glucose levels in obese woman aged 45-55 years.